Предмет: Алгебра,
автор: дана105
(a-2b)в кубп -(а+2b)в кубе
Ответы
Автор ответа:
0
(a-2b)³-(a+2b)³=(a³-6a²b+6ab²-8b³)-(a³+6a²b+6ab²+8b³)=
= a³-6a²b+6ab²-8b³-a³-6a²b-6ab²-8b³=-6a²b-6a²b-16b³=-12a²b-16b³=
=4b(-3a²-4b²)
= a³-6a²b+6ab²-8b³-a³-6a²b-6ab²-8b³=-6a²b-6a²b-16b³=-12a²b-16b³=
=4b(-3a²-4b²)
Автор ответа:
0
вы умница спасибо
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Українська мова,
автор: liliayaskiv2010
Предмет: Другие предметы,
автор: krutojigar685
Предмет: Информатика,
автор: Millaaa